1169. In Vitro Activity of Posaconazole versus Voriconazole for the Treatment of Invasive Aspergillosis in Adults Enrolled in a Clinical Trial. (31st December 2020) - Castanheira, Mariana; Woosley, Leah; Motyl, Mary; Han, Seongah; Campbell, Havilland
Abstract: Background: Invasive aspergillosis (IA) is a life-threatening disease with limited treatment options and is associated with delays in effective treatment and significant early mortality. Posaconazole (POS) is a broad-spectrum triazole antifungal, that exhibits potent activity against yeasts and molds. We evaluated the antifungal susceptibility profiles of isolates collected during a randomized, prospective, phase 3, double-blind, double-dummy study comparing posaconazole with voriconazole (1:1 randomization) given for ≤12 weeks in the primary treatment of IA (ClinicalTrials.gov, NCT01782131; EudraCT, 2011-003938-14) using CLSI and EUCAST reference testing methodologies. Methods: More than 90 study sites located in 23 countries enrolled subjects in the clinical trial. A total of 127 isolates were recovered from documented infections during 2013 through 2019. Fungal isolates were identified using molecular methods and antifungal susceptibility testing was performed by reference broth microdilution methods. The following antifungal agents tested were: posaconazole, itraconazole, voriconazole, caspofungin, and amphotericin B Results: Of the 127 samples tested, 119 were identified as Aspergillus species. Aspergillus fumigatus (N=76) was the most prevalent species, followed by A. flavus species complex (N=19), A. section Nigri (N=10), A. section Terrei (N=7). Overall, posaconazole (MIC50 /MIC 90, 0.5/1 mg/L) displayed similar activity to voriconazole (MIC50 /MIC90, 0.5/1 mg/L) and itraconazole (MIC50 /MIC90, 1/2 mg/L) against 119 Aspergillus species Isolates, by both, CLSI and EUCAST method. Posaconazole (MIC50 /MIC90, 0.5/0.5 mg/L) and voriconazole (MIC50 /MIC90, 0.25/0.5 mg/L) inhibited all 76 A. fumigatus isolates at MIC of 1 mg/L. Among 19 A. flavus species complex isolates recovered from this study, posaconazole (MIC50 /MIC90, 0.5/1 mg/L), voriconazole (MIC50 /MIC90, 1/1 mg/L) and itraconazole (MIC50 /MIC90, 0.5/1 mg/L) displayed equivalent activity. Conclusion: Posaconazole displayed good activity against all Aspergillus species isolates included in this study. In addition, posaconazole in vitro activity against Aspergillus species was similar to that observed by voriconazole and itraconazole. Disclosures: Mariana Castanheira, PhD, 1928 Diagnostics (Research Grant or Support)A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Amplyx Pharmaceuticals (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Fox Chase Chemical Diversity Center (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support)Pfizer (Research Grant or Support)Qpex Biopharma (Research Grant or Support) Leah Woosley, n/a, Merck & Co, Inc. (Research Grant or Support) Mary Motyl, PhD, Merck & Co, Inc (Employee, Shareholder) Seongah Han, PhD, Merck & Co, Inc. (Employee) Havilland Campbell, BS, Merck & Co, Inc. (Employee)